Allocating macro-prudential powers - Dirk Schoenmaker; Daniel Gros; Sam Langfield; Marco Pagano (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2014)
Monetary, macro-prudential and micro-prudential policies are intimately linked. The macroprudential authority should be allocated to the body where the overall balance of synergies (between policy objectives) over conflicts and the required expertise are the largest. This report reviews the pros and cons of the four institutional models for the allocation of macro-prudential powers: (1) the government, (2) the central bank, (3) the financial authority and (4) a committee with representatives from these three bodies.
Keywords: G28; 330; macroprudential regulation; economic policy; governance